Clinical Evaluation of Gamma Knife Stereotactic Radiosurgery for Metastatic Disease in Elderly Patients. (1st October 2022) - Bishr, Mai; Tancu, Cornel; Fersht, Naomi; Kitchen, Neil; Kosmin, Michael
Abstract: AIMS: Gamma Knife Stereotactic Radiosurgery (GK-SRS) is an effective treatment option for limited brain metastases (BM); however, there is a paucity of data about its use in the elderly. Our aim is to explore the clinical outcomes of elderly cancer patients treated for BM with GK-SRS at our institution. METHOD: We identified cancer patients aged ≥80 years at the time of receiving GK-SRS to BM between July 2017 and August 2021 from our electronic institutional database. Descriptive statistics and Kaplan–Meier analysis were performed using SPSS v.22. RESULTS: A total of 24 patients were identified, with a median age of 83 years (range 80.1-89.9). The most common primary tumours were melanoma (58.4%) and lung (20.8%). In 14 patients (58%), multiple BM were treated simultaneously with a median of 2 lesions (range 2-15). The median target volume was 1.34cc (range 0.03-15.06). Prescribed doses ranged from 18Gy – 25Gy, prescribed to the 41-97% isodose line. After a median follow-up of 6.9 months (range 1.9-49.4 months), the local control rate (LCR) was 91.3% and the median post-GK-SRS overall survival was 9.8 months (95%CI 5.4-14.3). This compares to our previously published data from our wider GK-SRS-treated BM patient cohort, which showed a median survival of 15.6 months and LCR of 94.6%. CONCLUSION: GK-SRS is an effective treatment modality for selected cancer patients with BM, including those over 80 years of age. Multi-institutional prospective studies are warranted to further explore the safety and functional outcomes of GK-SRS in elderly cancer patients.